Evaluasi Perhitungan Harga Pokok Air Minum dalam Menentukan Tarif Air Minum : Studi Kasus pada PDAM Tirta Pakuan Kota Bogor - Setiawan, H. Hendra; Wihandranti, Ade Wisni (Jurnal Ilmiah Ranggagading (JIR), 2006)
This research was done to find out the cost pricing of drinking water selling, the determination of drinking water rate and the correlation of the two. Itâs utilized case study method with hypothetical testing techniques as descriptive-comparative. The result indicates that the cost price calculation of drinking water selling has significant correlation to determining drinking water rate. The cost price of drinking water selling based on cost components was determined by using accounting cost average, financial average, and cost level (low cost, moderate cost and high cost level) as principle to determining drinking water rate structure based on customer group and water consumption block. Keywords: Cost Pricing